2016
DOI: 10.1186/s12862-016-0802-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern of genetic diversity and selection in the MHC class II DRB of three Neotropical bat species

Abstract: BackgroundAlthough bats are natural reservoirs of many pathogens, few studies have been conducted on the genetic variation and detection of selection in major histocompatibility complex (MHC) genes. These genes are critical for resistance and susceptibility to diseases, and host–pathogen interactions are major determinants of their extensive polymorphism. Here we examined spatial patterns of diversity of the expressed MHC class II DRB gene of three sympatric Neotropical bats, Carollia perspicillata and Desmodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 97 publications
(114 reference statements)
5
19
0
Order By: Relevance
“…The number of alleles detected per animal ranged from two to eight, indicating the existence of at least four DRB loci in A. pigra. This variation in the number of MHC-DRB loci between individuals of a species has been reported for several mammals, such as humans, other non-human primates, bats, tree shrews, and voles (Bontrop, 2006;Oppelt et al, 2010;Kloch et al, 2010;Salmier et al, 2016). These gene duplications contribute to MHC diversity and are known to play an important role in the adaptive evolution of organisms (Hughes and Yeager, 1998).…”
Section: Drb Loci and Lineagessupporting
confidence: 53%
“…The number of alleles detected per animal ranged from two to eight, indicating the existence of at least four DRB loci in A. pigra. This variation in the number of MHC-DRB loci between individuals of a species has been reported for several mammals, such as humans, other non-human primates, bats, tree shrews, and voles (Bontrop, 2006;Oppelt et al, 2010;Kloch et al, 2010;Salmier et al, 2016). These gene duplications contribute to MHC diversity and are known to play an important role in the adaptive evolution of organisms (Hughes and Yeager, 1998).…”
Section: Drb Loci and Lineagessupporting
confidence: 53%
“…Therefore, these 4 alleles and the corresponding 5 samples were removed from analysis, leaving 131 successfully genotyped individuals with 45 nucleotide alleles and 27 amino acid alleles. We identified 1 to 5 alleles (average 2 alleles) per individual, suggesting up to 3 loci of the DRB gene in the little brown bat (Table 1) and in line with observations of 1 to 3 loci in previously studied bat species (Mayer & Brunner, 2007;Real-Monroy et al, 2014;Richman et al, 2010;Salmier et al, 2016;Schad et al, 2011Schad et al, , 2012, except for the sac-winged bat which was identified with 10 loci (Schad et al, 2012). A significant but weak correlation (R 2 = 0.11, p < .01) was detected between the sequencing depth and the number of nucleotide alleles ( Figure S1), suggesting dropout of low-depth putative alleles due to differential amplification efficiency.…”
Section: Sampling and Identification Of Mhc Allelessupporting
confidence: 90%
“…Sequences translated into premature stop codons were removed from analysis, together with the samples in which these variants were found. vivesi (Richman et al, 2010), Noctilio albiventris (Schad et al, 2012), Saccopteryx bilineata (Schad et al, 2012), Carollia perspicillata (Schad et al, 2012), Desmodus rotundus (Salmier et al, 2016), and Artibeus jamaicensis (Real-Monroy et al, 2014). Codons of the antigen-binding sites were identified based on previous publications (Richman et al, 2010;Salmier et al, 2016).…”
Section: Identification Of Putative Allelesmentioning
confidence: 99%
“…These genes are affected by pathogen-mediated selection in a wide range of vertebrate species (Wegner et al 2003;Piertney and Oliver 2006;Savage and Zamudio 2011), and spatial patterns of variation in the MHC can serve as an immunogenetic proxy for the potential of a declining population to adapt to shifting selection by pathogens (Hawley and Fleischer 2012;Kyle et al 2014). The MHC has been studied in several bats, including a suite of Neotropical phyllostomid species (Schad et al 2012b;Real-Monroy et al 2014;Salmier et al 2016), the sac-winged bat (Saccopteryx bilineata; Mayer and Brunner 2007), and two North American Myotis species (M. velifer, M. velesi;Richman et al 2010). MHC variants are correlated with ectoparasite load in the lesser bulldog bat (Noctilio albiventris; Schad et al 2012a).…”
Section: Introductionmentioning
confidence: 99%